14th AIAA/CEAS Aeroacoustics Conference (29th AIAA Aeroacoustics Conference) 2008
DOI: 10.2514/6.2008-2961
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Fairings for Landing Gear Noise Control

Abstract: I. AbstractLanding gears of commercial aircraft make an important contribution to total aircraft noise in the approach configuration. Using fairings to shield components from high speed impingement reduces noise. Furthermore, perforating these fairings has been confirmed by flight tests to further enable noise reduction. Following a more fundamental study on the application of perforated fairings, a study has been performed to investigate and optimize the benefits of bleeding air through landing gear fairings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Examples are available in the literature of usage of porous fairing to further reduced noise of their solid counterpart. Boorsma et al 24 , for instance, successfully used perforated fairings applied to the articulation link of a generic four-wheel landing gear in order to reduce the effectiveness of the same solid concept. They showed that the noise reduction was significant in the low frequency range for which an increase took place when solid fairings were used.…”
Section: B Porous Brake Fairingsmentioning
confidence: 99%
“…Examples are available in the literature of usage of porous fairing to further reduced noise of their solid counterpart. Boorsma et al 24 , for instance, successfully used perforated fairings applied to the articulation link of a generic four-wheel landing gear in order to reduce the effectiveness of the same solid concept. They showed that the noise reduction was significant in the low frequency range for which an increase took place when solid fairings were used.…”
Section: B Porous Brake Fairingsmentioning
confidence: 99%
“…By streamlining the deployed landing gear, the turbulence generated by the landing gear elements, and thus the overall noise, can be reduced. [25] While the interaction itself is not very well understood, it has also been shown that the level of the noise produced scales with the 6 th power of local flow speed. Rather than streamlining the gear design, the technology implemented in this model employs slots placed upstream of the landing gear that blow air to create a "curtain" that deflects the free stream airflow around the landing gear and reduces the local flow velocity, as shown in Figure 2 (from Ref.…”
Section: Landing Gear Shielding With Blown Air Curtainsmentioning
confidence: 99%
“…Initial noise control solutions involved the application of solid add-on fairings to shield the complex noise generating parts of the landing gear structure from the flow [3][4][5][6], but there was evidence that flow displaced by such fairings could be detrimental because of additional noise from adjacent gear components that experienced increased local flow speeds. As a solution of this problem, porous fairings were developed to reduce the amount of displaced flow, whilst still providing a sufficiently low flow velocity in the wake of the fairing not to generate high interaction noise levels with the downstream gear components [7][8][9].…”
Section: Introductionmentioning
confidence: 99%